Implementasi Teknologi Green Economy pada Bisnis Keluarga Modern - Karimullah, Suud Sarim (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2024)
This study aims to identify the factors that influence the successful adoption of green economy technology, analyze its impact on business sustainability, and examine the role of family values in supporting this transformation. The library research method is used in this study, as it allows for an in-depth exploration of various existing theories, concepts, and empirical findings, to build a strong argumentative basis and produce a comprehensive synthesis of different perspectives. The results confirm that the green economy is a strategic imperative that requires family businesses to transform the traditional paradigm towards progressive long-term sustainability. The next generation, with their global vision and innovation courage, are the key actors in introducing green technologies, creating eco-friendly products, and integrating sustainability values into the core of family businesses. While there is often tension with the older, more conservative generation, cross-generational collaboration offers opportunities to create synergies between legacy stability and future innovation. If managed appropriately, family businesses will not only survive the dynamics of the modern economy but also lead the transformation towards a green economy that is equitable, inclusive, and has a positive impact on the environment and global society